Getting Started with Talend Open Studio for Data Integration. - Finnigan, Kenneth (Packt Pub., 2012)
7. Job Orchestration; What is a subjob; A simple subjob; On Subjob Error; On Component OK; Run If; Jobs as subjobs; Iterating and looping; Iterate connections; ForEach loop; Loop ""n"" times; Infinite loop; Duplicating and merging dataflows; Duplicating data; Merging data; Summary; 8. Managing Jobs; Job versions; Exporting and importing jobs; Exporting jobs; Exporting a project; Exporting a job; Exporting a job for execution; Importing jobs; Importing a project; Importing a job; Scheduling jobs; Summary; 9. Global Variables and Contexts; Global variables; Studio global variables.